Simultaneous Determination of Ripretinib and Its Desmethyl Metabolite in Human Plasma Using LC-MS/MS - Qian, Zhou-Yi; Wang, Ping; Wang, Zi-Yi; Zhao, Yang; Du, Tian-Tian; Xu, Hao; Wang, Yong-Qing; Sun, Lu-Ning (Therapeutic drug monitoring, 2024)
Ripretinib, a recently developed tyrosine kinase inhibitor with switch-control abilities, can inhibit both primary and secondary activation of KIT (KIT proto-oncogene receptor tyrosine kinase) and platelet-derived growth factor receptor alpha (PDGFRA) mutants, which contribute to gastrointestinal stromal tumor progression. In this study, a high-performance liquid chromatography-tandem mass spectrometry method to measure the concentrations of ripretinib and its active desmethyl metabolite DP-5439 in human plasma was developed and validated. Plasma samples were extracted and recovered by precipitation with acetonitrile containing the internal standard and diluted with acetonitrile before analysis. Ripretinib and DP-5439 were separated using chromatography on a Waters ACQUITY UPLC HSS T3 column (2.1 mm × 50 mm, 1.8 μm) with gradient elution using 0.1% formic acid and 5 mM ammonium formate in water as mobile phase A and acetonitrile as mobile phase B. The mobile phase was set to a flow rate of 0.5 mL/min. The calibration curves were linear across the following concentration range: 7.5 to 3000 ng/mL for ripretinib and 10 to 4000 ng/mL for DP-5439. The intraday and interday precisions were approximately 15% for all analytes in the quality control samples. The relative matrix effects in extracted plasma samples (90.3%-108.8% at different levels) were considered acceptable. This method will be a useful tool in oncology to facilitate the further clinical development of ripretinib.